Review Article: Potensi Farmakologi Bunga Telang (Clitoria ternatea) - Athallah, Dimas Rifqi; Rudiyanto, Waluyo; Wijaya, Sofyan Musyabiq; Angraini, Dian Isti (Medula, 2024)
Clitoria ternatea, commonly known as butterfly pea flower, is a tropical plant with high historical and cultural value, particularly in traditional medicine in Indonesia and Asia. This plant is rich in bioactive compounds such as phenols, terpenoids, and alkaloids, which contribute to its various pharmacological activities, including antioxidant, antidiabetic, antihyperlipidemic, anticancer, anti-inflammatory, antimicrobial, hepatoprotective, and neuroprotective effects. The phenolic compounds in the flower function as natural antioxidants, while terpenoids and alkaloids support antidiabetic and anticancer effects. This review aims to evaluate the pharmacological potential of C. ternatea based on literature published in the last decade (2014–2024), sourced from PubMed, Google Scholar, Science Direct, and ResearchGate. Inclusion criteria were articles in English and Indonesian, while exclusion criteria included incomplete access articles, secondary reviews, and studies with weak methodologies. Based on this review, C. ternatea shows great potential as an alternative modern therapy, with consistent research demonstrating significant therapeutic activity and low side effects. Its bioactive compounds work through mechanisms such as enzyme inhibition, glucose regulation, inflammation modulation, and protection from oxidative stress, making it a promising candidate for innovative therapeutic development.